2007
DOI: 10.1021/jp0740651
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurements of Intersystem Crossing Rates and Triplet Decays of Luminescent Conjugated Oligomers in Solutions

Abstract: Photothermal calorimetry and fluorescence spectroscopy were used to determine the relaxations of the photoexcited singlet state of two PPV and polyfluorene oligomers, (E,E)-1,4-bis[(2-benzyloxy)styryl]benzene (PVDOP) and ter(9,9'-spirobifluorene) (TSBF). The decay rates of different S1 relaxation channels, which include intersystem crossing (ISC), radiative, and nonradiative decay can be determined by the combination of photoacoustic calorimetry (PAC) and the time-correlated single photon counting (TCSPC) tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…It has been demonstrated that the nonradiative rates in metal-based systems are governed by the energy gap law, although deviations from a well-defined relationship are observed for low band gap energies <2.4 eV. Moreover, significant deviations from the predicted relationship are also observed, 40,41 especially in the transition between monomeric and polymeric structures. 42 The nonradiative rate also shows a deviation from the predicted exponential relationships when dealing with complexes wherein the structure varies from a homologous complex.…”
Section: ■ Resultsmentioning
confidence: 99%
“…It has been demonstrated that the nonradiative rates in metal-based systems are governed by the energy gap law, although deviations from a well-defined relationship are observed for low band gap energies <2.4 eV. Moreover, significant deviations from the predicted relationship are also observed, 40,41 especially in the transition between monomeric and polymeric structures. 42 The nonradiative rate also shows a deviation from the predicted exponential relationships when dealing with complexes wherein the structure varies from a homologous complex.…”
Section: ■ Resultsmentioning
confidence: 99%
“…In terms of heat relaxation, the PAC amplitude is proportional to the total yield of nonradiative decay paths, including intersystem crossing and internal conversion . For TSBF, it has been reported that the PAC amplitude (0.20, normalized with respect to HBP) is mainly contributed by internal conversion (ϕ IC = 0.09) and intersystem crossing (ϕ T = 0.06), whereas the contribution from volume change is negligible. , These fluorescence quantum yields (ϕ) of materials were measured at various concentrations by fluorescence spectrometer. Figure b shows the plot of integrated fluorescence intensity vs absorbance (varied by changing the solution concentration within the limit of 0.1 or less in optical density).…”
Section: Resultsmentioning
confidence: 99%
“…It is anticipated that direct measurement of relative conjugation across the imidazole bridge via Raman spectroscopy will elucidate both the complex relationship shown earlier and shortcoming of the energy gap law [35][36][37] when considering monomer to polymeric structures [38,39]. Figure 7 shows the linear variation of the luminescence yield as a function of the variation of the frequency of the imidazole ring stretch of the polypyridyl ligand.…”
Section: Results: Part I-effect Of Changing Electron Affinity Of the mentioning
confidence: 97%